2021
DOI: 10.21037/apm-20-1469
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of auricular acupressure for chemotherapy-induced peripheral neuropathy among patients with breast cancer: a study protocol for a randomized controlled trial

Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a frequently-reported distress symptom in breast carcinoma patients under chemotherapy. Although previous studies emphasized lack of ideal neuroprotective or therapeutic agents for CIPN, there are no strongly recommended treatments. Nevertheless, auricular acupressure (AA) is a novel remedy for controlling symptoms in many healthcare settings. However, therapeutic effects of AA among patients with CIPN have not yet been elucidated fully. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The AA intervention was provided for 6 weeks with 5 days of seed attachment and 2 days of rest as 1 cycle. The reflex points of the experimental group were shenmen, subcortex, sympathetic nerves, liver, and lumbar vertebrae, whereas using helix 1~5 points, which was the zone not corresponding to pain, neuropathy, and sleep and away from the reflex points of the experimental group, for the control group (Figure 2) [12,14]. The suitability of these points was consulted with two experts before the final selection.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AA intervention was provided for 6 weeks with 5 days of seed attachment and 2 days of rest as 1 cycle. The reflex points of the experimental group were shenmen, subcortex, sympathetic nerves, liver, and lumbar vertebrae, whereas using helix 1~5 points, which was the zone not corresponding to pain, neuropathy, and sleep and away from the reflex points of the experimental group, for the control group (Figure 2) [12,14]. The suitability of these points was consulted with two experts before the final selection.…”
Section: Interventionmentioning
confidence: 99%
“…Auricular acupressure (AA) is an economical, simple, and non-invasive intervention that does not have the risk of cross-infection or side effects; thus, it is considered a nursing intervention that can be performed independently by nurses instead of acupuncture for patients who have undergone spinal surgery [12]. In addition to pain, AA has been proven effective in sleep disorders [13] and neuropathy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies applied other scales for assessment [14,21,27,34,[42][43][44][45][46][47][48][49][50][51], involving 857 participants. One four-arm trial [43] conducted direct a comparison among Acu, hydroelectric baths (HEB), vitamin, and UCP, one study used ES, one three-arm study conducted a direct comparison among SMT, RT, and UCP [44], five studies used massage [27,42,45,46,51], four study used ME [34,47,48,50], and one study used PBM [21]. A close loop of the network map was formed by SMT, RT, and UCP.…”
Section: Peripheral Neuropathological Symptoms-other Scalesmentioning
confidence: 99%
“…Fifteen studies [14, 16, 18-20, 22, 26, 37, 44, 46, 49, 51, 57-59] reported sensory symptoms, involving 991 participants. Among the studies, two studies used interventions pooled as ES [14,16], 13 studies used UCP, two applied ME [37,57], four used studies pooled as massage [19,46,51,58], 3 applied Edu [20,22,59]. One three-arm trial conducted a direct comparison among SMT, RT, and UCP [44], and one study applied ET [37].…”
Section: Sensory Symptomsmentioning
confidence: 99%
See 1 more Smart Citation